Effect of Mydriasis-Caused Intraocular Pressure Changes on Corneal Biomechanical Metrics - Ye, Yufeng; Li, Yi; Zhu, Zehui; Abu Said, Anas Ziad Masoud; Nguelemo Mayopa, Kevin; Akiti, Stephen; Huang, Chengyi; Lopes, Bernardo T.; Eliasy, Ashkan; Miao, Yuanyuan; Wang, Junjie; Zheng, Xiaobo; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose: To evaluate the dependence of biomechanical metrics on intraocular pressure (IOP) Methods: 233 refractive surgery patients were included in this study – all were examined 3 times with the Corvis ST before and after dilation, and the differences (∆) in the main device parameters were assessed. The data collected included the biomechanically corrected IOP (bIOP), the central corneal thickness (CCT) and six dynamic corneal response (DCR) parameters, namely DA, DARatio2mm, IIR, SP-A1, CBI and SSI. Participants were divided into three groups according to the changes in patients’ bIOP after mydriasis. Results: Intra-operator repeatability was generally high in most of the DCR parameters obtained before and after dilation. The mean changes in bIOP and CCT after dilation were -0.12 ±1.36mmHg and 1.95 ±5.23μm, respectively. Only ∆DARatio2mm, ∆IIR and ∆CBI exhibited a statistically significant correlation with ∆CCT (p < 0.05). The changes in all DCR parameters, especially ∆DA and ∆SP-A1 were also correlated with ∆bIOP (p < 0.01) – a 1-mmHg change in bIOP was associated, on average, with 5.612 and -0.037 units of change in SP-A1 and DA, respectively. In contrast, the weakest correlation with ∆bIOP was exhibited by ∆SSI. Conclusions: Most corneal DCR parameters, provided by the Corvis ST, were correlated with IOP, and more weakly with CCT. Changes experienced in CCT and IOP should therefore be considered in studies on corneal biomechanics and how it is affected by disease progression and surgical or medical procedures.